Patient-reported symptoms and problems at admission to specialized palliative care improved survival prediction in 30, 969 cancer patients: A nationwide register-based study. (June 2020) - Hansen, Maiken B; Nylandsted, Lone Ross; Petersen, Morten A; Adsersen, Mathilde; Rojas-Concha, Leslye; Groenvold, Mogens
Background: Large, nationally representative studies of the association between quality of life and survival time in cancer patients in specialized palliative care are missing. Aim: The aim of this study was to investigate whether symptoms/problems at admission to specialized palliative care were associated with survival and if the symptoms/problems may improve prediction of death within 1 week and 1 month, respectively. Setting/participants: All cancer patients who had filled in the EORTC QLQ-C15-PAL at admission to specialized palliative care in Denmark in 2010–2017 were included through the Danish Palliative Care Database. Cox regression was used to identify clinical variables (gender, age, type of contact (inpatient vs outpatient), and cancer site) and symptoms/problems significantly associated with survival. To test whether symptoms/problems improved survival predictions, the overall accuracy (area under the receiver operating characteristic curve) for different prediction models was compared. The validity of the prediction models was tested with data on 5, 508 patients admitted to palliative care in 2018. Results: The study included 30, 969 patients with an average age of 68.9 years; 50% were women. Gender, age, type of contact, cancer site, and most symptoms/problems were significantly associated with survival time. The predictive value of symptoms/problems was trivial except for physical function, which clearly improved the overall accuracy for 1-week and 1-month predictions of death when added to models including only clinical variables. Conclusion: Most symptoms/problems were significantly associated with survival and mainly physical function improved predictions of death. Interestingly, the predictive value of physical function was the same as all clinical variables combined (in hospice) or even higher (in palliative care teams).